Peningkatan Kemandirian melalui Kegiatan Pembelajaran Pratical Life pada Kelompok Bermain Asoka Makassar - Andi Rezky Nurhidaya; Yuyun Gustiani (Universitas Muhammadiyah Enrekang, 2023)
This research aims to increase independence through practical life learning activities. The subjects in this research were 10 children from the Asoka Sudiang Makassar Kindergarten Play Group. Consisting of 7 men and 3 women and the subject's age range was 3-4 years. The type of research used was classroom action research which was conducted in two cycles and in each cycle was carried out in three meetings. The focus of this research is increasing independence through practical life learning activities. Research procedures include planning, implementing actions, observing and reflecting. The data collection techniques used are observation and documentation. The results of the study show that practical life learning can increase early childhood independence in Asoka Sudiang Makassar Kindergarten. This can be seen in the pre-action 31.5% in the criteria of not yet developing, the child's independence after being given action in cycle I increased to 51.87% in the criteria of developing according to expectations and in cycle II it increased to 84.37% in the criteria of very good development . With this practical life learning, it can be a solution to increase the independence of the children of the Asoka Sudiang Makassar Play Group.